Safety of Allogeneic Adipose Tissue-Derived Mesenchymal Stem Cells for the Treatment of Complex Perianal Fistulas Not Associated With Crohn's Disease: A Phase I Clinical Trial - Maciel Gutiérrez, Víctor Manuel; Gutiérrez Guillen, Sergio Giovanni; Centeno Flores, Manuel Willebaldo; Valenzuela Pérez, Jesús Alonso; Abarca Rendón, Francisco Manuel; Hernández García, Fernando Santiago; De la Cerda Trujillo, Liliana Faviola; Gómez Torres, Gustavo Ángel (Diseases of the colon & rectum, 2021)
Anal fistula treatment aims to eradicate the fistula, preserve the sphincter, prevent recurrence, and allow an early return to daily activities for the patient. Because of the difficulty of achieving these goals, stem cell-based therapy has emerged for the treatment of complex perianal fistula with promising results. The objective of this study was to evaluate the safety of allogeneic mesenchymal stem cells in the treatment of complex anal fistula in patients without Crohn's disease. This was a prospective nonrandomized phase I clinical trial. This study was conducted at a second-level hospital. Twenty consecutive patients diagnosed with a complex fistula were included. All patients received 40 × 106 allogeneic mesenchymal stem cells. In patients with 2 tracts, 20 × 106 stem cells were applied on each tract. The patients were discharged 24 hours after the procedure and were evaluated at 1, 2, 4, 8, 16, and 24 weeks after the application. The long-term follow-up was performed 1 year after the procedure. The procedure was performed in a total of 20 patients from October 1, 2016, to October 31, 2017; 1 patient was eliminated from the final data analysis. No adverse effects were reported within the first 24 hours, and all the patients were discharged asymptomatic. Three patients (15%) presented with perianal abscess. In 1 patient, the abscess appeared at the fourth week, and, in the other 2 patients, the abscess was diagnosed at week 8. Complete closure was achieved in 13 (69%) patients. This was a nonrandomized controlled trial. The use of allogeneic mesenchymal stem cells as a treatment is a safe option for the management of complex perianal fistula not associated with Crohn's disease. See Video Abstract at http://links.lww.com/DCR/B443. ANTECEDENTES:El tratamiento de la fístula anal tiene como objetivo erradicar la fístula, preservar el esfínter, prevenir la recurrencia y permitir un retorno temprano a las actividades diarias del paciente. Debido a la dificultad de alcanzar estos objetivos, ha surgido una terapia basada en células madre para el tratamiento de la fístula perianal compleja con resultados prometedores.OBJETIVO:El objetivo de este estudio fue evaluar la seguridad de las células madre mesenquimales alogénicas en el tratamiento de la fístula anal compleja en pacientes sin enfermedad de Crohn.DISEÑO:Este fue un ensayo clínico prospectivo no aleatorizado de fase I.AMBIENTE:Este estudio se realizó en un hospital de segundo nivel.PACIENTES:Veinte pacientes consecutivos diagnosticados de fístula compleja.INTERVENCIONES:Todos los pacientes recibieron 40 x 106 células madre mesenquimales alogénicas, en pacientes con dos tractos, se aplicaron 20 x 106 células madre en cada tracto.PRINCIPALES MEDIDAS DE RESULTADO:Los pacientes fueron dados de alta 24 horas después del procedimiento y fueron evaluados 1, 2, 4, 8, 16, 24 semanas después de la aplicación. El seguimiento a largo plazo se realizó un año después del procedimiento.RESULTADOS:El procedimiento se realizó en un total de 20 pacientes desde el 1 de octubre de 2016 al 31 de octubre de 2017; un paciente fue eliminado del análisis de datos final. No se informaron efectos adversos en las primeras 24 horas, todos los pacientes fueron dados de alta asintomáticos. Tres pacientes (15%) presentaron absceso perianal. En un paciente, el absceso apareció a la cuarta semana y en los otros dos pacientes el absceso se diagnosticó en la octava semana. El cierre completo se logró en 13 (69%) de los pacientes.LIMITACIONES:Este fue un ensayo controlado no aleatorio.CONCLUSIÓN:El uso de células madre mesenquimales alogénicas como tratamiento es una opción segura para el manejo de la fístula perianal compleja no asociada con la enfermedad de Crohn. Consulte Video Resumen en http://links.lww.com/DCR/B443.